2015
DOI: 10.1128/aem.03643-14
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Microbial Communities in Manganese Remediation Systems Treating Coal Mine Drainage

Abstract: cWater discharging from abandoned coal mines can contain extremely high manganese levels. Removing this metal is an ongoing challenge. Passive Mn(II) removal beds (MRBs) contain microorganisms that oxidize soluble Mn(II) to insoluble Mn(III/IV) minerals, but system performance is unpredictable. Using amplicon pyrosequencing, we profiled the bacterial, fungal, algal, and archaeal communities in four MRBs, performing at different levels, in Pennsylvania to determine whether they differed among MRBs and from surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Also of relevance, a recent study by Chaput et al . () demonstrated that Ascoymcete fungi were more prevalent than Basidiomycota (largely Agaricomycetes) in passive remediation systems that were most effective in treating high concentrations of dissolved Mn emanating from abandoned coal mines. Although the Chaput et al .…”
Section: Discussionmentioning
confidence: 99%
“…Also of relevance, a recent study by Chaput et al . () demonstrated that Ascoymcete fungi were more prevalent than Basidiomycota (largely Agaricomycetes) in passive remediation systems that were most effective in treating high concentrations of dissolved Mn emanating from abandoned coal mines. Although the Chaput et al .…”
Section: Discussionmentioning
confidence: 99%
“…All major microbial groups are capable of immobilizing metal ions and carrying out mineralization processes through organic and inorganic precipitation of secondary associated minerals as well as depositing crystalline material on and within cell walls [31,34,35]. Also, fungi have been reported as an important part of the microbial community of RĂ­o Tinto, as well as other mine drainage systems with similar characteristics (e.g., [7,[36][37][38]) So, in a scenario like RĂ­o Tinto, it is not unreasonable that fungi may be involved in different geochemical cycles, such as the dissolution of certain minerals and the formation of new ones.…”
Section: Resultsmentioning
confidence: 99%
“…RĂ­o Tinto, as well as other mine drainage systems with similar characteristics (e.g., [7,[36][37][38]) So, in a scenario like RĂ­o Tinto, it is not unreasonable that fungi may be involved in different geochemical cycles, such as the dissolution of certain minerals and the formation of new ones. Our TEM and HAADF-STEM analyses of the M13 sediments showed fungal cells involved in biomineralization processes with minerals nucleated on fungal cell walls (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Coal gangue, sandy soil, and clay (mass ratio 45:4:1) as goaf filling materials were investigated as an effective treatment method for the removal of Fe and Mn from mining drainage (Zhang et al, 2015). Experiments Pennsylvania (Chaput et al, 2015). The goal was to determine whether the communities differed among MRBs and the surrounding soil as well as establish the relative abundance of known Mn(II) oxidizers.…”
Section: Treatment Optionsmentioning
confidence: 99%